2007
DOI: 10.1016/j.bios.2007.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Living cell positioning on the surface of gold film for SPR analysis

Abstract: Living cell reactions are detected as changes of the angle of resonance (AR) for surface plasmon resonance (SPR). Since SPR reflects the events in the field of evanescence, cells need to be fixed on the sensor chip. In this study, we developed methods to fix living cells on a gold surface and to recover adherent cells from the culture dish, preserving their functions to be analyzed by SPR. Human basophils and B cells were fixed to the sensor chip by a biocompatible anchor for cell membranes (alpha-succinimidyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 16 publications
1
36
0
Order By: Relevance
“…Based on two of the above-mentioned reports, Yanase et al compared different methods to fix living cells on a SPR gold surface and to recover living and proliferating adherent cells, that could not be directly cultured on the surface, from the culture dish [93]. As sensoric elements, the group used two different types of cells: as non-adherent cell type, human basophils and B-cells were fixed to the sensor chip either by a biocompatible anchor for cell membranes, an aminoalkanethiol or an amino-reactive cross-linker.…”
Section: Surface Plasmon Resonance Analysis Of Eukaryotic Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on two of the above-mentioned reports, Yanase et al compared different methods to fix living cells on a SPR gold surface and to recover living and proliferating adherent cells, that could not be directly cultured on the surface, from the culture dish [93]. As sensoric elements, the group used two different types of cells: as non-adherent cell type, human basophils and B-cells were fixed to the sensor chip either by a biocompatible anchor for cell membranes, an aminoalkanethiol or an amino-reactive cross-linker.…”
Section: Surface Plasmon Resonance Analysis Of Eukaryotic Cellsmentioning
confidence: 99%
“…The different series of experiments conducted in this study identified aminoalkanethiols, like cysteamine, as the linkers of choice when it comes to an easily applicable and equally efficient surface immobilization of non-adherent cells. The transfer and recovery of adherent cells that are not directly grown on the sensor surface but on a culture dish and subsequently transferred to the sensor, works best with special culture dish materials fabricated from superhydrophile property or temperature-responsive polymers, that keep adherent cells in a quasi-floating state and make them easily removable by simple pipetting [93].…”
Section: Surface Plasmon Resonance Analysis Of Eukaryotic Cellsmentioning
confidence: 99%
“…Gold has been the most frequently investigated conductive material due to its ability to easily convey electrical shock to substrates during electrical charge stimulation of affected cells or tissues [5][6][7]. In biomedical fields, conductive gold films have been reported to enhance the proliferation and differentiation of adhered cells such as nerve and endothelial cells [8][9][10]. Thus, gold-coated surfaces have suitable biocompatibility, which indicates that they have the potential for biomedical applications [11][12][13].…”
Section: Introductionmentioning
confidence: 98%
“…In addition to these procedures, surface plasmon resonance (SPR) technique has been developed during recent two decades for investigation of interaction between two ingredients like antigen-antibody [18], cell-drug [19], drug-protein [20][21][22], DNA-RNA and etc [23]. Also calculation of reliable affinity and kinetics binding constants like association rate constant (ka), dissociation rate constant (kd) and affinity (KD) has been reported using SPR [24][25][26].…”
Section: Introductionmentioning
confidence: 99%